Improved diabetic wound healing by LFcinB is associated with relevant changes in the skin immune response and microbiota - Mouritzen, Michelle V. (2021)
Bovine lactoferricin (LFcinB) has antimicrobial and immunomodulatory properties; however, the effects on diabetic wound healing remain poorly understood. The wound healing potential of LFcinB was investigated with in vitro, ex vivo, and in vivo models. Cell migration and proliferation were tested on keratinocytes and on porcine ears. A type 1 diabetic mouse model was also used to evaluate wound healing kinetics, bacterial diversity patterns, and the effect of LFcinB on oxidative stress, macrophage phenotype, angiogenesis, and collagen deposition. LFcinB increased keratinocyte migration in vitro (p < 0.05) and ex vivo (p < 0.001) and improved wound healing in diabetic mice (p < 0.05), though not in normoglycemic control mice. In diabetic mouse wounds, LFcinB treatment led to the eradication of Bacillus pumilus, a decrease in Staphylococcus aureus, and an increase in the Staphylococcus xylosus prevalence. LFcinB increased angiogenesis in diabetic mice (p < 0.01), but this was decreased in control mice (p < 0.05). LFcinB improved collagen deposition in both diabetic and control mice (p < 0.05). Both oxidative stress and the M1-to-M2 macrophage ratios were decreased in LFcinB-treated wounds of diabetic animals (p < 0.001 and p < 0.05, respectively) compared with saline, suggesting a downregulation of inflammation in diabetic wounds. In conclusion, LFcinB treatment demonstrated noticeable positive effects on diabetic wound healing.